Rare occurrence of uterine arteriovenous malformation clinically mimicking a malignant growth - Trang K. Lollie; Steven S. Raman; Amir Qorbania; Ted Farzaneh; Neda A. Moatamed (University of São Paulo, 2021)
Arteriovenous malformation (AVM) is a rare lesion in the uterus, which can lead to abnormal uterine bleeding. While AVM has been described in other organs in the literature, there is a paucity of pathology reports of the AVM in uterus. On gross examination, the uterus was markedly enlarged and partly distorted with a pedunculated solid mass, which on the cut surface showed multiple well-circumscribed hemorrhagic cysts ranging from 0.1 to 4.0 cm in size. Microscopically, they were malformed dilated vascular structures containing organized thrombi. We present this case of uterine AVM with gross and microscopic findings, which can serve as a crucial reminder for pathologists to keep in the differential diagnoses as a potential cause of abnormal uterine bleeding.